(3TQM GdgGQhfjIs - (3YeQ Hf GdgQhj, fLe GdOjf,J (B700 (3g` s ((3Ydi Hf WhZGf s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg abO SCdfi GdCejQ Cf CLYd dg TQMkG s
(3BNQgG (B:s
(3hgh fGbU ef aYdd hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdKGfjs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdUQas